PENGARUH MODEL TWO STAY TWO STRAY TERHADAP HASIL PEMBELAJARAN IPS DI KELAS V SD - Santia, Yulpina; Arwin, Arwin; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this research is to find out about the significant effect of the use of the Two Stay Two Stray (TSTS) cooperative learning technique on the learning result of Social Science subject of the 5th grade students of Semen Padang Elementary School No1. The type of research used in quasi-experiment using the design of non-equivalent control group design. The samples of this study were students of the 5th grader in 5A and 5B class of Semen Padang Elementary School No1. The sampling technique used was saturated sampling. At the 5% significance level, the analysis result of the hypothesis test have  obtained tcalculation> ttable (2.44> 1.67). Based on the study results, it is concluded that there is a significant effect on the use of the Two Stay Two Stray (TSTS) cooperative learning technique on the students learning results in the social science subject. Keywords: Two Stay Two Stray, learning result, social science